2004
DOI: 10.1023/b:jots.0000038483.69570.5b
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behavioral couple's treatment for posttraumatic stress disorder: Initial findings

Abstract: This pilot study was an initial investigation of Cognitive-Behavioral Couple's Treatment (CBCT) for posttraumatic stress disorder (PTSD). Seven couples in which the husband was diagnosed with PTSD secondary to Vietnam combat experiences completed the treatment. According to independent clinician assessment and partner report, the veterans had substantial improvements in their PTSD symptoms. The veterans reported less dramatic improvements in their PTSD symptoms, but endorsed significant improvements in their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
152
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 15 publications
8
152
2
2
Order By: Relevance
“…Consistent with previous research, the veterans reported more modest improvements in their PTSD symptoms, but larger improvements in depression, anxiety, and social functioning. Wives reported large improvements in relationship satisfaction, as well as their general anxiety and social functioning (Monson, Schnurr, Stevens, & Guthrie, 2004;.…”
Section: Cognitive-behavioral Conjoint Therapy For Posttraumatic Strementioning
confidence: 98%
“…Consistent with previous research, the veterans reported more modest improvements in their PTSD symptoms, but larger improvements in depression, anxiety, and social functioning. Wives reported large improvements in relationship satisfaction, as well as their general anxiety and social functioning (Monson, Schnurr, Stevens, & Guthrie, 2004;.…”
Section: Cognitive-behavioral Conjoint Therapy For Posttraumatic Strementioning
confidence: 98%
“…However, supportive and emotionally intimate civilian family interactions with the returning veteran seem to protect against mental health problems. Family therapy sessions that include both the veteran and his or her family have been shown to successfully improve returning veterans' mental health outcomes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Veterans reported moderate effect size improvements in PTSD and statistically significant and large improvements in depression, general anxiety, and social functioning. Wives reported large effect size improvements in their relationship satisfaction, general anxiety, and social functioning [14].…”
Section: Va/dod Clinical Practice Guideline Regarding Couple/family mentioning
confidence: 97%
“…Evidence that the intervention is effective is lacking or poor quality, or conflicting, and the balance of benefits to harms cannot be determined" [8, p. 202]. The supporting evidence offered for this conclusion includes three studies: Devilly [9], Glynn et al [4], and Monson et al [10]. Upon review of these studies, the CPG summarizes that "BFT [behavioral family therapy] did not significantly improve the PTSD symptoms and was inferior to other psychotherapies" [8, p. 144].…”
Section: Va/dod Clinical Practice Guideline Regarding Couple/family mentioning
confidence: 99%
See 1 more Smart Citation